2019
DOI: 10.1007/s00198-019-05034-2
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive assessment of risk factors for falls in middle-aged adults: co-ordinated analyses of cohort studies in four countries

Abstract: A comprehensive assessment of risk factors for falls in middle-aged adults: coordinated analyses of cohort studies in four countries. Osteoporosis International.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 40 publications
3
23
1
3
Order By: Relevance
“…Falls were the dominating trauma mechanism (55%) with a marked increase from age group 50 years in line with recent studies (Steyerberg et al 2019). The late middle-aged (50-70 years) have recently been identified as a risk group, as they intersect with increasing comorbidity on one hand and keeping up physical and social activity on the other (Gale et al 2018;Peeters et al 2019). Thus, fall-preventing strategies ought to include this age-group as well.…”
Section: Discussionsupporting
confidence: 71%
“…Falls were the dominating trauma mechanism (55%) with a marked increase from age group 50 years in line with recent studies (Steyerberg et al 2019). The late middle-aged (50-70 years) have recently been identified as a risk group, as they intersect with increasing comorbidity on one hand and keeping up physical and social activity on the other (Gale et al 2018;Peeters et al 2019). Thus, fall-preventing strategies ought to include this age-group as well.…”
Section: Discussionsupporting
confidence: 71%
“…Of note, however, is that higher physical activity levels were associated with greater odds of falling in this sample of middle‐aged adults with OA. This differs to previous literature where adults over 50 years of age who were more active were less likely to fall (Peeters et al., 2019; Pereira, Baptista, & Infante, 2014; White et al., 2018). Given that no association was also observed between physical activity and falls in people with OA or those at high risk of developing OA (Soh et al., 2020), further work is needed to determine whether there may be a nonlinear association between mobility and falls in this group of individuals (Barker, Nitz, Low Choy, & Haines, 2012).…”
Section: Discussioncontrasting
confidence: 99%
“…We found that females were more likely to have fallen, which is consistent with patterns reported previously in both middle‐aged and older adults (Peeters, Cooper, Tooth, Schoor, & Kenny, 2019; World Health Organization, 2008), although prior studies have tended to include more women. Policies and programmes related to falls prevention may need to reflect a gender perspective.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, it is known that low atmospheric pressure can cause headaches, a feeling of dizziness and decreases in blood pressure among weather-sensitive people [ 47 , 48 , 49 ]. The association between dizziness and falls among middle-aged adults was found by Peeters et al [ 50 ] during the analysis of data from population-based cohort studies in Australia and the UK. One possible explanation for the phenomenon observed in our study is that days with average air temperatures and atmospheric pressures may be the most comfortable for outdoor activities, and thus the higher incidence could be due to higher outdoor exposure.…”
Section: Discussionmentioning
confidence: 76%